2016
DOI: 10.1111/dpr.12202
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Investment Treaties and Foreign Direct Investment: Evidence of Asymmetric Effects on Vertical and Horizontal Investments

Abstract: Bilateral investment treaties (BITs) are legal instruments used by developing and transition countries to provide investor protection and, by extension, promote higher levels of inward foreign direct investment (FDI). While the link between BITs and FDI has been extensively studied, little is known about the impact of the treaties on different forms of investment. Motivated by this observation, we examine the effects of BITs on vertical and horizontal FDI. We find that BITs are more positively related to verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…In general, we find that the horizontal motive is the primary reason for FDI for UK-based MNEs. Such result differs from existing studies, which typically find the importance of the vertical motive (Sirr et al, 2017;Maza et al, 2020). Our baseline analysis demonstrates that BITs act as a market access tool, resulting in a decrease of the horizontal type of inward FDI in a host economy.…”
Section: Discussioncontrasting
confidence: 89%
“…In general, we find that the horizontal motive is the primary reason for FDI for UK-based MNEs. Such result differs from existing studies, which typically find the importance of the vertical motive (Sirr et al, 2017;Maza et al, 2020). Our baseline analysis demonstrates that BITs act as a market access tool, resulting in a decrease of the horizontal type of inward FDI in a host economy.…”
Section: Discussioncontrasting
confidence: 89%
“…When FDI inflow is used as the dependent variable to test for robustness, results are consistent and show that BITs are not significant. These findings lend credence to studies employing BITs to examine their signalling role on FDI (Büthe & Milner, 2009;Falvey & Foster-McGregor, 2018;Sirr et al, 2017). Although Tobin and Rose-Ackerman (2011) and Yackee (2007) argued that the effect of BITs was more robust in countries with better institutions, Neumayer and Spess (2005) contended that BITs act as substitutes and, therefore, are more productive in countries with weaker institutions.…”
Section: Resultsmentioning
confidence: 67%
“…Many empirical studies have found that ratified BITs significantly attract FDI (Busse et al, 2010; Haftel, 2010; Sirr et al, 2017). Notwithstanding these findings, results in this study corroborate those of Aisbett (2007), Yackee (2007, 2011) and ECA (2016), who found BITs to be trivial for FDI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final monadic study covered here is by Sirr, Garvey, and Gallagher (2017). The study covers 28 developing and transition countries from 1999-2008 and specifically investigates whether BITs have differentiated effects on vertical and horizontal FDI.…”
Section: Bits As a Form Of Signaling (The Monadic Approach)mentioning
confidence: 99%